2018
DOI: 10.1159/000490596
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Surgery and the Unknown Primary

Abstract: Carcinoma of unknown primary (CUP) comprises approximately 1%–5% of all head and neck malignancies. Primary site detection rates for metastatic cervical squamous cell carcinoma (SCC) remain variable, with current diagnostic imaging unable to identify all tumours. Prevailing evidence suggests that most head and neck CUP are located in the oropharynx. Diagnostic surgical efforts have been directed at sampling the entire oropharynx. Present techniques that make this possible include transoral robotic surgery (TOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…According to Enyinnaya et al, N1 type was found in 1%, N2 in 69.5% and N3 in 32% 24. Similar results were obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…According to Enyinnaya et al, N1 type was found in 1%, N2 in 69.5% and N3 in 32% 24. Similar results were obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with unknown primary neck metastasis commonly go through an array of examinations, such as flexible endoscopic assessment, palpation of the tonsils and base of the tongue, and PET-CT. If the primary tumor remains elusive, TORS palatine and lingual tonsillectomy can be employed as part of the staging algorithm (42). The lymphoepithelial tissue of the tongue base from the circumvallate papillae to vallecula can be removed by TORS (26).…”
Section: Extended Applications Of Torsmentioning
confidence: 99%
“…2,9 However, literature suggests PET-CT provides additional primary tumour detection rates in HNCUP over conventional imaging techniques in 37-44% of cases with a sensitivity and specificity of 97% and 68%, respectively. 10 Specifically, data suggest identification of sub-centimetre lesions is of particular difficulty (and in this case the lesion being 9 mm). Consequently, TORS provides a useful adjunct for Head and Neck surgeons and patients in identifying a primary lesion that is smaller than the resolution offered by PET CT, which can often be the case with HPV-positive patients who experience early metastasise with bulky lymph nodes.…”
Section: Discussionmentioning
confidence: 92%